Effects of Saccharomycopsis fibuligera and Saccharomyces cerevisiae inoculation on small fermentation starters in Sichuan-style Xiaoqu liquor - Su, Chang; Zhang, Kai-Zheng; Cao, Xin-Zhi; Yang, Jian-Gang (Food research international, 2020)
[Display omitted] •We aimed to improve the flavor profile of Xiaoqu liquor.•We added Saccharomycopsis fibuligera and Saccharomyces cerevisiae to the culture.•Analysis revealed increased diversity of Xiaoqu liquor.•We elucidated the chemical composition and main microorganisms involved. Xiaoqu liquor is a type of distilled spirit in China prepared on a small scale from a small solid starter culture. Although this liquor is popular in southwestern China, it can have a dull taste, limiting its market. To improve the flavour profile of Xiaoqu liquor, we selected two functional yeast strains (Saccharomycopsis fibuligera and Saccharomyces cerevisiae) from Zaopei (fermented grain) of Baijiu liquor and used them for Xiaoqu liquor fermentation. Compared with traditional Xiaoqu (Starter), bioaugmentation inoculation increased the glucoamylase and acidic protease activities and the ethanol synthesis rate, while decreasing the acidity of the Zaopei (fermented grains) in the early stage of fermentation. By the end of the fermentation process, the alcohol and ester content had also increased by 42.5% and 11.8%, respective, and that of aldehydes and ketones, and heterocyclic compounds decreased by 73.7% and 77.1%, respectively. Traditional isolation and high-throughput sequencing were employed to analyse the microorganisms in the Zaopei. Bioaugmentation inoculation increased the microbial diversity of Xiaoqu liquor during the fermentation process. The dominant fungus during fermentation using the two types of starter cultures was S. cerevisiae, whereas the dominant bacteria was Pseudomonas, followed by Bacillus, Weissella, Lactobacillus, and Bacteroides. Principal component analysis of the bacterial community structure and flavour substances in the Zaopei produced using the two strains revealed that there were few differences between the two liquors and that inoculation with functional yeasts may not change the flavour substances in Xiaoqu liquor. However, correlation analysis showed that Escherichia Shigella, Terrisporobacter, Bacillus, Clostridium, and Prevotellaceae are the main microorganisms in the Xiaoqu liquor fermentation process. These results lay the foundation to improve the quality of Xiaoqu liquor.